Islamic thought of Ahmad Domocao Alonto (1914-2002) : a critical analysis - Disomimba, Mohammad Nashief S. (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study examines Ahmad Domocao Alonto's Islamic Thought (AIT) and his major contributions in the development of Islamic thought in the Philippines. The general elements of AIT requires a discourse analysis, which attempts to integrate texts, contexts, and intertexuality in understanding Islām as the foundation of Alonto's overall approach as a Muslim scholar, intellectual, leader, and reformist. The study argues that AIT is premised on Islām as shown in the sources of Alonto's writings and speeches, and his Western education is articulated and blended with the Islamic perspective. The sources of AIT are the Holy Qurān and the hadĪth of Prophet Mohammad (peace be upon him). Although Alonto was not proficient in Arabic, the 12 respondents commended his resoluteness to spread Islām to the Muslims in Mindanao. In the synthesis and evaluation of Alonto's approach and contributions to Islamic thought in the Philippines, the respondents confirmed that they are based on the following: reflections on the five pillars of Islām and explications of Islamic concepts such as Birr, Taqwā, freedom, equality, brotherhood, morality and peace. In combining sound understanding of the role of Islām and effective articulation of social reforms, Alonto exorcised his fears to confront colonization and Christianization by his active participation in the Philippine Senate. The concrete manifestations of his Islamic Thought are Jāmitu al-FilibbĪn al-Islāmia, Ansār al-Islām Movement, education, national integration, autonomy, civil service, international relations with the Muslim world, and Inter-faith dialogue. Alonto became the voice of the Muslims in counteracting the military atrocities of then president Ferdinand E. Marcos in the late 1950s and late 1970s. The apex of Alonto's mission to provide the Muslims freedom to govern themselves was realized in the 1987 Philippine Constitution, which enshrined the provisions in granting local autonomy to Muslim Mindanao. Ahmad Domocao Alonto left a legacy to his people, unsurpassed by other Muslim Filipino leaders before his time, and he contributed to the development of Islamic thought and its dissemination in modern ways and approaches.